1991
DOI: 10.1037/0033-2909.109.2.340
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of response time distributions: An example using the Stroop task.

Abstract: The shape of a response time (RT) distribution can be described by a 3-parameter model consisting of the convolution of the normal and exponential distributions, the ex-Gaussian. Analyses based on mean RT do not take the distributions shape into account and, for that reason, may obscure aspects of performance. To illustrate the point, the ex-Gaussian model was applied to data obtained from a Stroop task. Mean RT revealed strong interference but no facilitation, whereas the analysis based on the ex-Gaussian mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
590
5
6

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 496 publications
(652 citation statements)
references
References 29 publications
34
590
5
6
Order By: Relevance
“…In contrast, numerous studies have reported ex-Gaussian analyses of the standard Stroop effect. Across these investigations a consistent pattern has emerged, such that the Stroop effect is seen in all three ex-Gaussian parameters (see Balota et al 2010;Heathcote et al 1991;Spieler et al 1996).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…In contrast, numerous studies have reported ex-Gaussian analyses of the standard Stroop effect. Across these investigations a consistent pattern has emerged, such that the Stroop effect is seen in all three ex-Gaussian parameters (see Balota et al 2010;Heathcote et al 1991;Spieler et al 1996).…”
mentioning
confidence: 72%
“…These results replicate previous reports in the literature (e.g., Augustinova & Ferrand, 2012;Augustinova et al 2010;Augustinova et al 2015;Labuschagne & Besner, 2015;Manwell et al 2004). According to reports by Spieler et al (1996) and Heathcote et al (1991), the standard Stroop effect yields effects on the mean of the normal distribution (mu), the standard deviation of the normal distribution (sigma), and the tail (tau). In contrast, an ex-Gaussian analysis of the combined data from Experiments 1, 2, 3, and 4 here yielded an SSE only in mu; the null effect in tau was particularly small (the scaled JZS Bayes factor of 8.9 is considered positive evidence in favor of the null; Wagenmakers, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As Heathcote et al (1991) have pointed out, relying on analyses of means alone can potentially lead to inadequate or misleading conclusions. In this instance, distributional analyses and analyses of means yielded markedly divergent outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…It is becoming increasingly clear that the analysis of mean RTs alone is not only inadequate but can sometimes be misleading (Andrews & Heathcote, 2001;Balota & Spieler, 1999;Heathcote, Popiel, & Mewhort, 1991;Plourde & Besner, 1997;Spieler, Balota & Faust, 1996;Yap, Balota, Cortese, & Watson, 2006). In particular, failing to take the shape of the distribution into account may obscure more subtle aspects of performance.…”
Section: Additive Effects and Models Of Word Recognitionmentioning
confidence: 99%
“…As RT distributions are usually not normally distributed but positively skewed (Heathcote et al, 1991), this procedure allows a more comprehensive analysis of RT data and therefore provides a more detailed characterization of pharmacological effects than traditional RT measures, enabling, for example, the analysis of RT variability. Distributional RT analyses have already been applied in prior studies using location-cueing paradigms (Gottlob, 2004;Vossel et al, 2006).…”
Section: Statistical Analysis Of Behavioral Datamentioning
confidence: 99%